Seeing yourself through others' eyes: A study of spontaneously occurring images in social phobia - Hackmann, A; Surawy, C; Clark, D (Cambridge University Press, 1998)
A recent cognitive model of social phobia suggested that negative self-images may play an important role in maintaining the disorder. To investigate this suggestion, 30 social phobics and 30 non-patient controls were given a semi-structured interview which focused on spontaneously occurring images. Social phobics were significantly more likely than controls to report experiencing images when anxious in social situations. In addition, social phobics' images were significantly more negative and significantly more likely to involve seeing oneself from an observer's perspective. Implications of these findings for the understanding and cognitive treatment of social phobia are discussed.